Chemicals for Agriculture exhibit board - Rohm and Haas Company (1956)
General view of an exhibit panel on agricultural chemicals, including fungicides, miticides, and emulsifiers, exhibited at the 1956 Rohm and Haas Company stockholders' meeting. The Rohm and Haas Company was founded in 1907 in Esslingen, Germany through the partnership of German chemist Otto Röhm and German businessman Otto Haas. In 1933, Röhm's experiments with the polymerization of methyl methacrylate led to the creation of a clear, solid plastic sheet, which he trademarked Plexiglas. During World War II, the demand for Plexiglas, which both Allied and Axis forces used for submarine periscopes and aircraft windshields, canopies, and gun turrets, helped transform Rohm and Haas into a major chemical firm.
Keywords: Rohm and Haas Company; Corporations; Agricultural chemicals; Chemical industry; Fungicides; Pests--Control; Agricultural pests--Control